A Financial Social Accounting Matrix for the Integrated Macroeconomic Model for Poverty Analysis : Application to Cameroon with a Fixed-Price Multiplier Analysis - Christian A. Emini; Hippolyte Fofack (World Bank: Washington, DC, 2013)
Cameroon is engaged in the Poverty Reduction Strategy Paper (PRSP) process, which emphasizes increased focus on poverty reduction in the design and implementation of growth and adjustment strategies. The Integrated Macroeconomic Model for Poverty Analysis (IMMPA) recently developed at the World Bank provides an analytical structure for supporting the PRSP process and quantifying poverty reduction strategies. Drawing on that framework, the authors provide a detailed financial social accounting matrix (SAM) for the Cameroonian economy to serve as input into the construction of an IMMPA model for Cameroon. An analysis of this financial SAM shows that the dramatic fall in investment during the crisis period persisted in the post-devaluation growth period in the late 1990s. Continued low investment has implications for ongoing high unemployment rates and poor welfare indicators. The authors illustrate this with simulations based on fixed-price multiplier analysis that highlight the potential growth and welfare benefits of increased public investment, following hypothetical debt relief and reduction of external debt servicing within the framework of the heavily indebted poor countries initiative.